Nanosheet architecture of Cu9S5 loaded with Fe3O4 microspheres for efficient electromagnetic wave absorption. Issue 7 (1st April 2021) - Liao, Jun; Ye, Mingquan; Han, Aijun; Guo, Jianming; Chen, Chenlu
Abstract: The high efficiency electromagnetic (EM) waves absorbers are in urgent need to eliminate EM pollution in view of the rapid development of electronic information technology. In this work, the pure Cu9 S5 nanosheet and Cu9 S5 /Fe3 O4 (CF) composites are prepared via hydrothermal method. Through the characterization of phase, morphology and the EM parameters, we found that the combination of dielectric loss component Cu9 S5 and magnetic loss component Fe3 O4 play a significant role in eliminating EM waves. In the discussion, we focused on comparing the EM wave absorption performance of the pure Cu9 S5 and CF composites. Further, by adjusting the mass ratio of CF to paraffin wax, the samples with different microwave absorption performance can be obtained. Among them, samples of the pure Cu9 S5 and 50%wtCF/paraffin showed excellent EM waves absorption performance. The 50%wtCF/paraffin exhibited the strongest RL value of −39.5 dB at the matching thickness of 4.3 mm, followed by the pure Cu9 S5, which the RL value is −20.5 dB at 1.3 mm with the EAB of 2.7 GHz. The structural features, good impedance matching and the combined effect of multiple loss mechanisms are the main reasons for making it an excellent EM absorber. This study will provide a new sight to fabricate an outstanding EM wave absorber. Graphical abstract: Image 1